Coexisting with the dynamic PU, the effect of PU‐returns on a secondary network. (31st March 2017) - Amini, Mohammad Reza; Mahdavi, Mehdi; Omidi, Mohammad Javad
Summary: Coexisting with a dynamic primary user network is a challenge in cognitive radio networks, since the rate at which primary user reoccupies the spectrum is high. Therefore, it is important to investigate deeply the effect of primary traffic dynamics on secondary network performance metrics. To do that, interference due to both sensing error and primary user re‐occupancy must be formulated and considered in throughput and collision probability. Besides them, secondary packet retransmissions due to such interference should be considered in metrics such as average energy consumption and average packet delay. In this study, we formulate the mentioned secondary network metrics regarding to such kinds of interference and secondary packet retransmission. Numerical results along with discussions are given to clarify derived expressions. Simulations are also performed to justify the theoretical results, and optimum operating point for secondary network settings is derived by genetic algorithm. Abstract : 1‐formulation of throughput, energy consumption, delay, and percentage of collision considering PU re‐occupancy and SU re‐transmissions 2‐ investigation of the PU ON‐OFF rate on network metrics